Green-phosphor Ca3Sc2Si3O12:Ce3+ for solid-status illumination: gel-combustion structural and luminous characteristics - Huu Phuc Dang; Bui Van Hie; Nguyen Le Thai (Institute of Advanced Engineering and Science, 2022)
Ca3Sc2Si3O12:Ce3+ phosphors with one stage and tiny dimension were effectively produced utilizing the gel-combustion technique at a lower heat (1100◦C) than the traditional solid-status reaction technique (around 1500◦C). The phosphors' crystal phase and microstructure, as well as their luminescence, were studied. The particle size is around 1m, which is significantly smaller than what the solid-status process produces. When particles are combined of silicon and deposited on a blue light-emitting diode (LED), finer particles can minimize interior diffusing. A significant green radiation is noticed that is caused by typical Ce3+ transition radiations 5d–2F5/2 and 5d–2F7/2. The stimulation spectra reveal a wide and high absorptivity at around 460 nm, indicating that it would be an excellent color conversion in white LEDs. The gel-combustion phosphor has a decay period of 54.65 ns.